2010
DOI: 10.1186/1755-7682-3-24
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic reward system: a short integrative review

Abstract: Memory is an essential element to adaptive behavior since it allows consolidation of past experience guiding the subject to consider them in future experiences. Among the endogenous molecules that participate in the consolidation of memory, including the drug-seeking reward, considered as a form of learning, is dopamine. This neurotransmitter modulates the activity of specific brain nucleus such as nuclei accumbens, putamen, ventral tegmental area (VTA), among others and synchronizes the activity of these nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
185
0
9

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(198 citation statements)
references
References 74 publications
4
185
0
9
Order By: Relevance
“…By providing information about the individual value and significance of environmental stimuli, these dopaminergic projections profoundly influence behavior and modulate higher brain functions (Arias-Carrion et al 2010;Bromberg-Martin et al 2010). Between species, pronounced differences in magnitude and complexity of cortical dopaminergic innervation have to be taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…By providing information about the individual value and significance of environmental stimuli, these dopaminergic projections profoundly influence behavior and modulate higher brain functions (Arias-Carrion et al 2010;Bromberg-Martin et al 2010). Between species, pronounced differences in magnitude and complexity of cortical dopaminergic innervation have to be taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, the D1R partial agonist ((+/−)-1-phenyl-2,3,4,5-tetrahydro-(1H)-3-benzazepine-7, 8-diol hydrochloride) (SKF-38393) also decreased alcohol intake in both rats (Cohen et al 1999;Dyr et al 1993;Silvestre et al 1996) and mice (Ng and George 1994). We are focusing on D1 receptors expressed in medium spiny neurons, because they are expressed at high levels in the ventral striatum (Caille et al 1996;Matamales et al 2009;Muly et al 2010;Podda et al 2010) and are thought to be major regulators of dopaminergic neurons originating from the ventral tegmental area (VTA) that provide innervation to the NAc (Altier and Stewart 1999;Arias-Carrion et al 2010;Cooper 2002;Gonzales et al 2004;Herz 1997;McBride et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…At present, the mechanism of methamphetamine addiction is not clear, but previous studies have shown that methamphetamine addiction is associated with the dopamine reward system in the ventral tegmental area of the brain [21]. Methamphetamine is an indirect agonist of dopamine that promotes the release of monoamine neurotransmitter [22][23].…”
Section: Mechanisms Of Psychiatric Diseasementioning
confidence: 92%